Assessing the Impact of Elevated Temperature and Water Limitation on Yield Production, and Seed Longevity of Aerobic Rice cv. MRIA 1 - Amirullah, Nurulnathasa; Abdul Rahman, Siti Maslizah; Aani, Siti Nur Anisah; Sinniah, Uma Rani (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
This research was conducted at the Faculty of Plantation and Agrotechnology, Universiti Teknologi MARA (UiTM) from February to May 2021. The study objectives were to determine the effects of environmental factors, water limitation (WL) and high temperature (HT), on yield production and seed quality development of aerobic rice cv. MRIA 1. The seed was cultivated in a glass house (25/45°C min/max) and subjected to 3 days of WL and HT (25/40ºC 12 photoperiod) at different seed development stages [8, 14, 21, and 28 days after anthesis (DAA)] with four replications. Plants treated from 21 to 28 DAA showed tolerance to WL and HT, while the detrimental effect occurred at 8 DAA and 14 DAA. Normal germination (>90%) was obtained from the control, and the plant had reached physiological maturity at 21 and 28 DAA. As plant treated to environmental stress, the amylose concentration obtained ranges from 9 to 14%. The lowest seed longevity (p50) obtained from plants treated at 14 DAA recorded only 3 days, and the longest was from control seed obtained for 26 days. In conclusion, exposing cv. MRIA to HT and WL at late maturation stage has less effect on yield production and seed quality development.